Analisis Kepuasan Pengguna Rekam Medis Elektronik Pada Unit Rawat Jalan Dengan Metode End User Computing Satisfaction (EUCS) Di Puskesmas Ngemplak Boyolali - Ifta Nirmawati; Sri Wulandari; Aris Widiyoko (Sekretariat Program Studi Sarjana Terapan Manajemen Informasi Kesehatan Politeknik Indonusa Surakarta., 2024)
Electronic Medical Records is an information system technology that is very important to support the quality of service. Ngemplak Boyolali Health Center has implemented RME on June 14, 2023. To determine the level of success in implementing RME, a user analysis is carried out to determine the level of end user satisfaction using the EUCS method. This study aims to determine user satisfaction with electronic medical records in the outpatient unit at the Ngemplak Boyolali Health Center. This research uses a qualitative method with a descriptive approach. The results of the research on the content aspect of RME are in accordance with user needs. In the accuracy aspect, RME has provided fairly accurate information. In the aspect of appearance (format) RME is very easy for users to use. In the aspect of ease of use, users find it easy to operate RME. In the timeliness aspect, the information provided by RME to users is very timely. At the user satisfaction level, users feel quite satisfied with the performance provided and the features provided by RME. In the man factor, user knowledge is good and RME is quite in accordance with user expectations. In the mechine factor, the internet network is stable, maintenance of infrastructure facilities is carried out regularly and the performance provided by the computer is fast enough. In the material factor, the hardware used is in accordance with user needs.